Development of a Training Strategy Aimed at Increasing Veterinarians’ Awareness of the Proper Use of Antibiotics on Rabbit Farms - Stefania Crovato; Francesca Menegon; Giulia Mascarello; Anna Pinto; Anna Nadin; Gloria Piovan; Guido Ricaldi; Guido Di Martino; Giandomenico Pozza (Animals, 2023)
The rabbit sector faces significant challenges with antimicrobial usage (AMU) and antimicrobial resistance (AMR). A focus group involving nine rabbit sector stakeholders identified key issues contributing to high AMU and the need for veterinarians’ training. Participants emphasized the lack of clear legislation, biosecurity standards, and the importance of training on best practices to reduce AMU. To address these concerns, a blended learning course for rabbit veterinarians was organized, focusing on responsible drug use to lower AMU. The course design promoted participant interaction using group exercises and online discussions. The output was an operational tool, encompassing crucial elements to reduce drug dependence, covering housing, environmental conditions, feed, reproduction, disease prevention, diagnosis, and treatments. Validated in veterinarians’ daily practices, the tool proved valuable. The tool, presented as a checklist, assists veterinarians in supporting field activities regarding proper drug use and AMR issues. It also helps farmers address knowledge gaps in breeding management and adopt biosecurity practices for disease prevention. Participants were encouraged to use the tool during farm visits and collaborate with farmers. The project presented in the manuscript is a crucial step towards the development of effective strategies for responsible AMU and AMR mitigation in the rabbit sector and beyond.